Avaliação do farelo integral de pimenta rosa (Schinus terebinthifolius Raddi) como promotores de produção na dieta de frangos de corte - Gonçalves, Fabiano Gomes (2011)
The aim of these studies was to evaluate, a first experiment, chemical composition of whole Brazilian red pepper meal (BRPM) and its use in the broilers diet with base on performance and liver function. A second experiment was to evaluate the inclusion of whole Brazilian red pepper meal (BRPM) associated or not with antibiotic growth promoters on performance, intestinal morphometry and on liver function in broiler diet. In the first experiment a total of 396 day-old male chicks, Cobb, distributed in a randomized design of three treatments and six replicates of 22 broilers each, constituted of the negative control - basal diet without growth promoter or whole Brazilian red pepper; positive control – basal diet with zinc bacitracin and salinomycin; diet with 1.2% BRPM. It was determined the concentration of phenolic compounds in all experimental diets, as well as whole meal. Regarding the chemical composition of the BRPM it was verified that the ether extract, crude fiber, calcium, total phenolics, total and condensed tannins were higher than in corn, although other nutrients such as protein and phosphorus have values close those observed in this grain. There was no difference (P>0,05) between treatments on animal performance. The BRPM reduced (P<0,05) the concentrations of alanine aminotransferase (ALT) and gamma glutamyltransferase (GGT) enzymes at 21 and 41 days old, respectively, compared to the CN, without compromising the weight gain (P>0,05). In the second experiment a total of 528 day-old male chicks, Cobb, distributed in a randomized design in groups of six treatments and four replicates of 22 birds each: T1: Negative Control (NC) - basal diet without BRPM or antibiotics; T2: Positive Control (PC) - basal diet with 1,2% BRPM; T3: PC + 11ppm zinc bacitracin and 17ppm salinomycin, T4: PC + 22ppm zinc bacitracin and 34ppm salinomycin; T5: PC + 33ppm zinc bacitracin and 51ppm salinomycin; T6: PC + 45ppm zinc bacitracin and 67ppm salinomycin. At 21 days of age it was observed elevated values of aspatate aminotransferase (AST) in broilers fed diet BRPM associated with higher additions of antibiotics compared to the others (P<0.05). Serum concentrations of AST, ALT and GGT in broiler chickens fed diet with 1.2% of BRPM did not differ from negative control at 21 and 41 days old. In period of 1-43 days-old, it was observed that the inclusion of BRPM with or without growth promoter reduced (P<0,05) feed intake and improved feed gain ratio compared with NC. It was observed that the broilers fed diet with antibiotics associated with the BRPM, in amounts up to 22mg/kg of zinc bacitracin and 34mg/kg of salinomycin resulted on higher of villus height compared with NC. It was concluded that partial substitution of corn by BRPM did not reduce the animal performance and that can be used to replace antibiotic growth promoters without decrease on animal performance, viability and production factor. The supplementation of 1.2% BRPM did not influence liver function and the inclusion of high doses of antibiotics associated with the BRPM resulted in hepatic dysfunction.